Pengaruh Set Kesempatan Investasi Terhadap Hubungan Antara Kepemilikan Manajerial dan Aliran Kas Bebas dengan Tingkat Leverage Perusahaan - Endang Raino Wirjono (KINERJA, 2009)
Agency  theory  mentions  that  leverage  (debt)  is  one  of  mechanism  used  by shareholders  to minimize agency problem with manager. In this context, previous researchers show that leverage was influenced by free cash flow and insider ownership (managerial ownership). This research aims  to  examine  the determinants  of  leverage  in  a  research  model  and  treats investment opportunity  set  (IOS)  as  moderating  variable  that  will  influence the  relationship  between  free cash flow and managerial ownership with leverage. By using sample consist of 38 manufacturing companies, result from moderated Regression Analysis (MRA) statistically shows evidence that IOS  influences  the relationship  between  free  cash  flow  and  leverage.  This  result supported Tarjo’s research (2002).